Identification of the bioactive compounds and antioxidant, antimutagenic and antimicrobial activities of thermally processed agro-industrial waste. (15th September 2017) - Vodnar, Dan Cristian; Călinoiu, Lavinia Florina; Dulf, Francisc Vasile; Ştefănescu, Bianca Eugenia; Crişan, Gianina; Socaciu, Carmen
Highlights: Phenolic content and antioxidant, antimicrobial and antimutagenic activity increased by thermal process (T). Monounsaturated fatty acids increased significantly by T in all 5 agro-food wastes. Polyunsaturated fatty acids decreased significantly by T in all 5 agro-food wastes. Abstract: The purpose of the research was to identify the bioactive compounds and to evaluate the antioxidant, antimutagenic and antimicrobial activities of the major Romanian agro-industrial wastes (apple peels, carrot pulp, white- and red-grape peels and red-beet peels and pulp) for the purpose of increasing the wastes' value. Each type of waste material was analyzed without (fresh) and with thermal processing (10 min, 80 °C). Based on the obtained results, the thermal process enhanced the total phenolic content. The highest antioxidant activity was exhibited by thermally processed red-grape waste followed by thermally processed red-beet waste. Linoleic acid was the major fatty acid in all analyzed samples, but its content decreased significantly during thermal processing. The carrot extracts have no antimicrobial effects, while the thermally processed red-grape waste has the highest antimicrobial effect against the studied strains. The thermally processed red-grape sample has the highest antimutagenic activity toward S. typhimurium TA98 and TA100.